Knowledge Attitude and Perceptions Regarding Shade Selection of Anterior Teeth among the Dental Professionals of Ghaziabad: A Kap Study: Assessing Knowledge, Attitude, and Practices on Shade Selection of Anterior Teeth among Dental Professionals in Ghaziabad (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Background Aim – Aesthetics has become a major concern in the current era in treatment planning. Reproducing the color of a natural tooth with artificial replacement still possesses a great challenge in modern dentistry.The present cross- sectional study was done to evaluate the knowledge, attitude and practices regarding shade selection of anterior teeth amongst the dental practitioners, post graduates interns of Ghaziabad.Methodology – A cross sectional study was conducted amongst a randomly selected sample of 390 dentists of Ghaziabad city. A validated, structured, self-administered questionnaire comprising of 20 closed ended questions was distributed to assess KAP regarding shade selection. Descriptive analysis Pearson’s Chi square test was applied keeping level of significance p